KUALITAS PELAYANAN PUBLIK DI MARKAS KOMANDO DIREKTORAT KEPOLISIAN PERAIRAN DAN KELAUTAN KEPOLISIAN DAERAH SULAWESI TENGAH - Wakhid, Abdul (Katalogis, 2019)
This research aims to find out the public service quality of Information in Headquarter Commander of Water and Air Police Directorate of Regional Police Department in Central Sulawesi. This was a descriptive qualitative research. Data used were primary and secondary data. Data collection was conducted through observation, interview, documentation and triangulation.Â  Informants were selected using purposive sampling technique. Data analysis used was adopted from Miles and Huberman model, namely data reduction, data display, and drawing conclusion. Theory used was from Parasuraman et al, consisted of five aspects, such as: 1) Tangibles, 2) Reliability, 3) Responsiveness, 4) Assurance, and Empathy. Based on the research findings, the public service quality of Information in Headquarter Commander of Water and Air Police Directorate of Regional Police Department in Central Sulawesi is not effective yet. The reason is as follow: first, tangibles aspect, which have insufficient facilities. Second is, reliability aspect, the quick response of the officers in giving service is not maximal yet because of limited personnel owned by the Regional Police Department in Central Sulawesi. Third, responsiveness aspect, that is the member of police personnel who received complaints by applicant have been good already, but the quick response in solving the complaints is not maximal yet, because the internet connection in several areas is not good. Fourth, assurance aspect, which is security assurance given by the police officers to the public is maximal already. Fifth, empathy aspect, where service given by the members of the police is not discriminative and they always provide service politely. Therefore, the researcher drawn conclusion that the public service quality of Information in Headquarter Commander of Water and Air Police Directorate of Regional Police Department in Central Sulawesi have not been maximal because of two aspectsÂ  have been fulfilled, while the other ones have not been fulfilled.